Fixed dried red blood cells and method of use - Fischer, Thomas; Read, Marjorie; Bode, Arthur P.; Nichols, Timothy (My University, 2005)
Fixed-dried red blood cells (RBCs), and processes for preparing the same are disclosed. The red blood cells, upon reconstitution with distilled water or appropriate buffer: bind oxygen with native affinities, have partial deformability, present minimal thrombogenicity to platelets, and have oblated blood group antigens. The RBCs are preferably fixed by means of cross-linkers with aldehyde functions such as paraformaldehyde or glutaraldehyde either alone or in combination. Native oxygen kinetics are achieved by preparing the red blood cells with 1,6-diphosphofructose. Blood group antigens and chemical functions that render the lyophilized RBCs thrombogenic are occluded by chemically attaching polyoxyethylene glycol polymers to the surface membrane of the red blood cells. The cross-linked red blood cells are preferably died by lyophilization.